Body, gender, adolescence: discourse and (other/new) meanings on anorexia and obesity - Régia Oliveira (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
The text aims to discuss issues related to the biomedical comprehension of eating disorders in adolescence and those ones related to the parents of the young girls diagnosed with these disorders, especially with anorexia/anorexia nervosa who try to understand and to take care. It aims to apprehend how the parents of the adolescents, diagnosed with anorexia, consider the normative discourse from the health professionals on body and how to take care of the adolescent and how they mean them in new/other ways or even escape from them due to the references from their sociocultural context. These reflections come from a current research that has been developed after a doctoral dissertation at the Federal University of São Paulo, UNIFESP, in Social Sciences. In relation to conclusions, it can be highlighted: the normative aspect of biomedical science; suffering of the family during the process of the disease; the search for taking care and for information about the anorexia; tensions in family relations, especially among parents and the young people considered to be ill; the search for partnership among health professionals and families in order to take care.